2383. In Vitro Activity of Ceftolozane–Tazobactam in Comparison With Ceftazidime–Avibactam vs. Antimicrobial Non-Susceptible Pseudomonas aeruginosa Clinical Isolates, Including Multidrug-Resistant and Extensively Drug-Resistant Subsets: CANWARD, 2007–2017. (26th November 2018) - Walkty, Andrew; Adam, Heather J; Baxter, Melanie; Lagace-Wiens, Philippe; Karlowsky, James; Hoban, Daryl; Zhanel, George
Abstract: Background: Pseudomonas aeruginosa (PA) is an important nosocomial pathogen. Treatment options for infections caused by multidrug-resistant (MDR) and extensively drug-resistant (XDR) isolates remain limited. Ceftolozane-tazobactam (C/T) and ceftazidime–avibactam (CZA) are two newer antimicrobials with antipseudomonal activity. The purpose of this study was to directly compare the in vitro activity of C/T and CZA vs. antimicrobial non-susceptible (NS) PA clinical isolates obtained as part of the CANWARD study. Methods: Annually from 2007 to 2017, sentinel hospitals across Canada submitted blood, respiratory, urine, and wound isolates (consecutive, one per patient/infection site) from patients attending ERs, medical and surgical wards, hospital clinics, and ICUs (CANWARD). Susceptibility testing was performed using broth microdilution (and breakpoints) as described by CLSI. MDR PA were defined as isolates that tested NS to at least one antimicrobial from ≥3 classes. XDR PA were defined as isolates that tested NS to at least one antimicrobial from ≥5 classes. Results: 4224 PA isolates were obtained as a part of CANWARD. 628 (14.9%) were MDR, and 129 (3.1%) were XDR. The in vitro activity of C/T and CZA (plus relevant comparators) is presented below. Conclusion: The in vitro activity of C/T was superior to CZA vs. antimicrobial NS PA clinical isolates (including MDR and XDR isolates) recovered from patients across Canada. Disclosures: D. Hoban, Abbott: Research relationship, Research support. Achaogen: Research relationship, Research support. Astellas: Research relationship, Research support. Merck Canada: Research relationship, Research support. Merck USA: Research relationship, Research support. Paratek Pharma: Research relationship, Research support. Pharmascience: Research relationship, Research support. Sunovion: Research relationship, Research support. Tetraphase: Research relationship, Research support. The Medicines Co.: Reserch relationship, Research support. Zoetis: Research relationship, Research support. G. Zhanel, Achaogen: Research relationship, Research support. Astellas: Research relationship, Research support. Merck Canada: Research relationship, Research support. Merck USA: Research relationship, Research support. Paratek PHarma: Research relationship, Research support. Pharmascience: Research relationship, Research support. Sunovion: Research relationship, Research support. Tetraphase: Research relationship, Research support. The Medicines Co.: Research relationship, Research support. Zoetis: Reserch relationship, Research support.